2020
DOI: 10.3390/insects11020134
|View full text |Cite
|
Sign up to set email alerts
|

First Insight into Microbiome Profiles of Myrmecophilous Beetles and Their Host, Red Wood Ant Formica polyctena (Hymenoptera: Formicidae)—A Case Study

Abstract: Formica polyctena belongs to the red wood ant species group. Its nests provide a stable, food rich, and temperature and humidity controlled environment, utilized by a wide range of species, called myrmecophiles. Here, we used the high-throughput sequencing of the 16S rRNA gene on the Illumina platform for identification of the microbiome profiles of six selected myrmecophilous beetles (Dendrophilus pygmaeus, Leptacinus formicetorum, Monotoma angusticollis, Myrmechixenus subterraneus, Ptenidium formicetorum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 128 publications
1
8
1
Order By: Relevance
“…In turn, Fischer et al (2017) have shown that bacteria may contribute to the recognition of distant aphid species by Lasius niger ants (Fischer et al 2017). These results strengthen interest in studying the role of microorganisms in shaping relationships among closely associated species (Szenteczki et al 2019;Kaczmarczyk-Ziemba et al 2020).…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…In turn, Fischer et al (2017) have shown that bacteria may contribute to the recognition of distant aphid species by Lasius niger ants (Fischer et al 2017). These results strengthen interest in studying the role of microorganisms in shaping relationships among closely associated species (Szenteczki et al 2019;Kaczmarczyk-Ziemba et al 2020).…”
Section: Introductionmentioning
confidence: 65%
“…The microbiota of Lasius fuliginosus and Pella laticollis 2019; Szenteczki et al 2019;Kaczmarczyk-Ziemba et al 2020)). In the present study, we have extended the state of the art regarding the microbiota of ants and their associates by investigating the potential similarities among the bacterial communities associated with two closely interacting species, L. fuliginosus and P. laticollis (both larvae and adults).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations